Stress and the gut-brain axis: an inflammatory perspective - Morys, Julia; Małecki, Andrzej; Nowacka-Chmielewska, Marta (Frontiers in Molecular Neuroscience, 2024)
The gut-brain axis (GBA) plays a dominant role in maintaining homeostasis as well as contributes to mental health maintenance. The pathways that underpin the axis expand from macroscopic interactions with the nervous system, to the molecular signals that include microbial metabolites, tight junction protein expression, or cytokines released during inflammation. The dysfunctional GBA has been repeatedly linked to the occurrence of anxiety- and depressive-like behaviors development. The importance of the inflammatory aspects of the altered GBA has recently been highlighted in the literature. Here we summarize current reports on GBA signaling which involves the immune response within the intestinal and blood-brain barrier (BBB). We also emphasize the effect of stress response on altering barriers' permeability, and the therapeutic potential of microbiota restoration by probiotic administration or microbiota transplantation, based on the latest animal studies. Most research performed on various stress models showed an association between anxiety- and depressive-like behaviors, dysbiosis of gut microbiota, and disruption of intestinal permeability with simultaneous changes in BBB integrity. It could be postulated that under stress conditions impaired communication across BBB may therefore represent a significant mechanism allowing the gut microbiota to affect brain functions.